Impact of Software Optimization on Variable Lifetimes in a Microprocessor-Based System - Bergaoui, S; Leveugle, R (2011 IEEE 6th International Workshop on Electronic Design, Test and Application, 2011)
Assessing and improving the level of system robustness with respect to soft errors has become one of the main design challenges, especially when designing critical embedded systems. In systems using microprocessors (e.g. most of SoCs) the system dependability is strongly correlated with the variable lifetimes. In this paper, we discuss the impact of compilation optimizations on the lifetimes in both memory blocks and internal processor registers. Evaluations on many significant examples show that specific optimization options are required when the reliability is more important than execution time or code size.